2020
DOI: 10.1002/fsn3.1786
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Astragalus Membranaceus supplementation on oxidative stability of Cashmere goat

Abstract: In livestock production, astragalus membranaceus (traditional Chinese herbal medicine) can improve its growth performance and antioxidant capacity, working as antioxidants to scavenge free radicals, and enhance the body's immunity and disease resistance. The advantages of Astragalus have no residue and side effects. In the previous studies, as a feed additive, the improvement of antioxidant capacity and meat quality of astragalus membranaceus are more common in pigs, chickens, geese, etc. But their application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…The present result about reducing the ratio of acetate and propionic acid with CMP and compound treatment indicated that diet with Chinese medicine polysaccharide improved rumen fermentation mode. In line with the result, adding 15 g/kg Astragalus polysaccharides to the lamb diet increased the concentration of propionic acid and reduced the ratio of acetate and propionic acid in rumen fluid ( 11 ). Ammonia–nitrogen (NH 3 -N) in the rumen is the main nitrogen source for the synthesis of microbial protein, and its normal concentration range is 6.3–27.5 mg/dl ( 30 ).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The present result about reducing the ratio of acetate and propionic acid with CMP and compound treatment indicated that diet with Chinese medicine polysaccharide improved rumen fermentation mode. In line with the result, adding 15 g/kg Astragalus polysaccharides to the lamb diet increased the concentration of propionic acid and reduced the ratio of acetate and propionic acid in rumen fluid ( 11 ). Ammonia–nitrogen (NH 3 -N) in the rumen is the main nitrogen source for the synthesis of microbial protein, and its normal concentration range is 6.3–27.5 mg/dl ( 30 ).…”
Section: Discussionsupporting
confidence: 64%
“…Astragalus polysaccharide has been reported to be a potential additive used in the vaccination of humans and animals so as to improve immune functions both in cellular and humoral immune responses ( 10 ). Astragalus polysaccharide was reported to enhance the antioxidant capacity while adding to the diet of goats ( 11 ). Furthermore, a recent report showed that L. barbarum polysaccharide (LBP) improved growth promotion and immunomodulation and could be used as an alternative for nutritive additive in broilers ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…This result could be positive because consumers generally do not expect to find high b* in fresh meat [63]. Similarly, previous studies [46,64] reported that supplementation with medicinal plants containing saponins, polysaccharides, and flavonoids also did not affect the colouration of meat from lambs and goats.…”
Section: Discussionmentioning
confidence: 61%
“…These findings suggest that the HM used could increase muscle hypertrophy, which would partially explain the observed reduction in b*. On the other hand, Luo et al [64] reported that dietary supplementation of medicinal plants containing saponins, polysaccharides and flavonoids altered the pigment content on the meat of small ruminants. Similar effects of consumption of these metabolites would partially explain the b* changes in the meat of lambs supplemented with HM in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…Studies have also evaluated the antioxidant effects of plant extracts on animal products. Luo et al [ 115 ] investigated the antioxidant effects of Astragalus membranaceus supplementation on goat muscles. The results showed that Astragalus membranaceus supplementation increased myoglobin content and the activities of some antioxidant enzymes (SOD and catalase), and it improved the values of free radical scavenging ability and cupric reducing antioxidant capacity in goat muscle, but it decreased the contents of metmyoglobin and MDA, indicating an enhanced antioxidant capacity in the goats.…”
Section: Application Of Plant Extracts In Ruminantsmentioning
confidence: 99%